Harmonic Voltage Distortions in Power Systems Due to Non Linear Loads - Aryan Kaushik; Jyothi Varanasi (International Journal of Applied Power Engineering (IJAPE), 2014)
Harmonics are found to have deleterious effects on power system equipments including transformers, capacitor banks, rotating machines, switchgears and protective relays. Transformers, motors and switchgears may experience increased losses and excessive heating. Shunt filters are effective in minimizing voltage distortions. This paper describes the voltage distortions generated by non linear loads. The harmonic specifications such as harmonic factor, characteristic harmonic and non-characteristic harmonic are considered while explaining the paper. ‘MiPower’ software is used to compute the harmonic distortions in a sample power system. Accurate harmonic models are established for a non linear load. To reduce the harmonic voltages impressed upon specific parts of the sample power system, passive filters are installed at two buses. With the implementation of a passive filter at the bus with non linear load, the harmonics are greatly reduced. For the specified power system, at all the buses the total harmonic distortion has been evaluated.